Academic Stress and Study Habits of Health Science University Students - Shetty, Sukesh; Kamath, Neetha; Nalini, M. (Journal of Health and Allied Sciences NU, 2021)
Introduction Academic stress and study habits are crucial indicators of academic success. At the moment, faulty study habits press on the students into academic stress. The present study was conducted to identify the academic stress and study habits of university students of health science.Methods This cross-sectional descriptive survey was conducted among 150 undergraduate students of nursing, physiotherapy, and pharmacy (n = 50 in each group). A stratified random sampling technique was used to select the study participants. The information on academic stress and study habits was collected by using the Student Stress Inventory and Palsane and Sharma Study Habit Inventory, respectively.Results Mean score of academic stress was found to be 75.353 ± 16.463. Pharmacy students had a higher level of stress compared to physiotherapy and nursing students (p = 0.013). Furthermore, the prevalence of unsatisfactory study habits among undergraduate students was 72%, with a mean score of 52.7 ± 9.152. Also, nursing students had a higher level of study habits compared to physiotherapy and pharmacy Students. There was no significant relationship found between study habits and academic stress (r = −0.048, p = 0.557). There was a significant association found between study habits and gender (p = 0.021), as well the association found between stress level and course type, Pre-University Course percentage, and first-year percentage (p = 0.044, 0.04, and 0.044 respectively).Conclusion Academic stress and poor study habits are prevalent among undergraduate students. This indicates strategies need to be formed to enhance healthy study habits and alleviate the academic stress of the students, mainly in professional courses; it is an urgent need.
Keywords: academic stress; study habits; undergraduate students